Genetic and Epigenetic Changes Caused by Pesticide Exposure are Associated with the Development of Chronic Diseases in Humans: A Systematic Literature Review - Fitriia, Friska Eka (RADINKA JAYA UTAMA PUBLISHER, 2024)
Inadvertently, pesticides can poison humans or livestock through the mouth, skin and inhalation. Often without realizing it, these toxic chemicals enter a person's body without causing sudden pain and resulting in chronic poisoning. Some people are less efficient at metabolizing environmental chemicals, placing them at higher risk of disease. from parents to children, or occur randomly due to exposure to certain factors. The aim of this research is to examine the genetic and epigenetic changes caused by pesticide exposure that are associated with the development of chronic diseases in humans. This research uses a systematic literature review using Preferred Reporting Items for Systematic Reviews (PRISMA). The research results show that changes in the body can certainly affect health which are related to changes in the way genes work and the Three Basic Classes of Epigenetic Mechanisms Methylation is the process of adding chemical chains to the DNA structure. This cannot be separated from several mechanisms of action of pesticides in attacking humans, which results in the development of several chronic diseases in humans due to exposure to pesticides.